1999
DOI: 10.1111/j.1532-5415.1999.tb02988.x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial of Outpatient Comprehensive Geriatric Assessment Coupled with an Intervention to Increase Adherence to Recommendations

Abstract: A single outpatient comprehensive geriatric assessment coupled with an adherence intervention can prevent functional and health-related quality-of-life decline among community-dwelling older persons who have specific geriatric conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
145
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 215 publications
(154 citation statements)
references
References 49 publications
5
145
0
4
Order By: Relevance
“…Community-based care: assessment followed by referrals and recommendations (N = 4) Eligible participants for these four studies were identified by a self-administered postal questionnaire (Robichaud et al 2000;Hebert et al 2001), telephone interview (Silverman et al 1995), or an interviewer-assisted selfadministered screening (Reuben et al 1999). Extensive assessment was performed by a nurse during home visits (Hebert et al 2001;Robichaud et al 2000) or by a team in community-based clinics (Reuben et al 1999;Silverman et al 1995).…”
Section: Transmural Care (N = 7)mentioning
confidence: 99%
“…Community-based care: assessment followed by referrals and recommendations (N = 4) Eligible participants for these four studies were identified by a self-administered postal questionnaire (Robichaud et al 2000;Hebert et al 2001), telephone interview (Silverman et al 1995), or an interviewer-assisted selfadministered screening (Reuben et al 1999). Extensive assessment was performed by a nurse during home visits (Hebert et al 2001;Robichaud et al 2000) or by a team in community-based clinics (Reuben et al 1999;Silverman et al 1995).…”
Section: Transmural Care (N = 7)mentioning
confidence: 99%
“…The comprehensive geriatric assessment (CGA) is considered by many to be the "gold standard" and is an effective clinical tool for identifying frailty in elderly patients (13,14). The CGA has demonstrated utility for the management of various geriatric problems including prevention of institutionalization and maintenance of independence, prevention of delirium in hospitalized patients, falls, and hospital readmission (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…When paired with outreach to improve adherence to recommendations among primary care clinicians, comprehensive assessment has preserved physical function and improved health-related quality of life among highrisk elders. 4 Other geriatric interventions with close links to primary care have been associated with reduced risk of hospitalization, including: a senior center-based disability prevention program, 5 multidisciplinary team primary care emphasizing chronic disease self-management, 6 and primary care-based group medical visits. 7 Positive studies, however, contrast with studies of brief outpatient geriatric interventions that have found little or no effects on clinical outcomes or health service use.…”
mentioning
confidence: 99%